International marketing strategy of Portuguese SMEs: case of Casa Ermelinda Freitas - Severino, Hugo Virgílio Teixeira Santos (2019)
Our reality as consumers is increasingly globalized and the borders of the countries no longer present as barriers to our most exquisite tastes. Nowadays, with a simple internet connection, we already can buy products from all corners of the world and the same is also true for all small and medium-sized enterprises that want to put their products on sale in the international markets, in order to expand their customer networks and increase their profits. Casa Ermelinda Freitas, led by recognized and acclaimed Leonor Freitas, is one of the major examples of the success of Portuguese family owned businesses abroad. Throughout this dissertation, the entering strategy used by the Portuguese company will be carefully detailed and explained so that it is possible to fully understand what steps were taken and what recommendations to draw from its success. In addition to the strategy, all necessary resources will be analyzed in the preparation and development of international markets, assessing the critical factors for this process. Finally, we will discuss the adaptations made at the product level, the distribution channels used, the pricing strategy and all the promotional means involved.